New record of Epistylis obliqua Sommer, 1951 (Ciliophora, Peritrichia) on aquatic mite Unionicola minor (Soar 1900) (Acari, Hydrachnidia) - Abibulaeva, Alie; Yalçin, Çağri; Durucan, Furkan; Dovgal, Igor (Zootaxa, 2023)
This article deals with the report of a colonial peritrich ciliate species Epistylis obliqua Sommer, 1951 as epibiont on hydrachnid mite Unionicola minor (Soar 1900) from the freshwater in Amsterdam, the Netherlands. The finding of the species is the first after its original description as well as the first finding on a mite which belongs to family Unionicolidae Oudemans, 1909. The systematic position, improved diagnosis and morphometrics characteristic of E. obliqua are presented in the present study.